Critical discourse analysis of misogyny and sexism in South Korea: Media sources studies - Susanti, Tia Ayu; Taufiq, M. Aries; Indriyani, Vivi; Irwan, Irwan; Shila, Nur Nabila (Universitas Islam Negeri Ar-Raniry, 2025)
Misogyny and sexism have become prominent issues in society, particularly in the workplace and daily life. Examining the role of media narratives in shaping public perception and framing events to serve specific agendas or ideologies can offer diverse perspectives. This study conducts of discourse analysis of two media sources: the BBC World Service video